The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Le travail social: théories, méthodologies et pratiques - Dorvil, Henri; Harper, Elizabeth; Bibliothèque numérique canadienne (Firme) (Collection Problèmes sociaux & interventions sociales, 2013)
"Ce livre vise à introduire de nouvelles façons de concevoir, de théoriser et d'intervenir sur le social en ce xxie siècle. Il y est non seulement question des fondements du travail social, mais aussi des politiques sociales, des méthodes d'intervention et des enjeux contemporains de la profession. En revisitant d'une manière créative les postulats de base du travail social, les auteurs proposent des lectures inédites des problèmes sociaux, un regard plus nuancé sur les populations marginalisées, un renouvellement des politiques sociales comme levier de citoyenneté ainsi que des pistes d'intervention plus respectueuses des individus, des groupes, des familles et des communautés."-- Site de l'éditeur.
Keywords: approche interculturelle; approches et analyses; cours; discipline; histoire et politique; intersectionnalité; outils; ouvrages de références; premier cycle; sciences humaines; sciences sociales; sex2283; thématiques; travail; travail social